1H NMR Study of the Lipid Composition, Oxidative and Hydrolytic Status of the Covering Oils of Canned Sardines After Long-Term Storage - Encarnacion Goicoechea-Oses (Foods)
The covering oils of twenty-two commercially canned sardines were studied by Proton Nuclear Magnetic Resonance spectroscopy (1H NMR) freshly purchased and also after storage at room temperature for fifteen years. The filling oils studied were olive oils (one extra-virgin olive oil), sunflower oils, soybean oils, and vegetable oils (unspecified origin). The aim was to obtain qualitative and quantitative information on lipid composition, oxidative and hydrolytic status, and on the changes occurring during storage. Just after purchase, in all the samples, the migration of fish omega-3 polyunsaturated eicosapentaenoic (EPA, C20:5ω3) and docosahexaenoic (DHA, C22:6ω3) acyl groups was reported; the occurrence of oxidative or hydrolytic reactions was not observed. After storage, the main change in the spectra was the presence of signals due to hydrolytic compounds (mainly 1,3-diglycerides, together with 1,2-diglycerides, 1-monoglycerides, and lower proportions of 2-monoglycerides). In eleven samples very low concentrations of saturated aldehydes (alkanals) were detected, which is considered a low oxidative status. It is suggested that the above-mentioned partial glycerides and alkanals migrated from sardine muscle to the oils. The content in omega-3 lipids in the oils after storage indicated the occurrence of lipid interchange between the sardine muscle and the packing oil in both directions.